ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI BAHAN BAKAR MINYAK (BBM) PADA SPBU 54.861.02 PT BOLAWOLON - Pare, Klemensia; Nona Dince, Maria; Niken Aurelia, Pipiet (Jurnal Projemen UNIPA, 2025)
This research was conducted at Public Fuel Filling Station (Stasiun Pengisian Bahan Bakar Umum/SPBU)54.861.02 PT Bolawolon with the objective of analyzing the accounting information system for cash sales of Fuel Oil (Bahan Bakar Minyak). This study employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings revealed that task overlapping still occurred, as operators also performed sales, cash handling, and delivery functions, while the manager also undertook warehouse and accounting functions. In addition, the documentation used was still limited to fuel purchase recommendation letters, purchase receipts, and bank deposit slips. The accounting records were also incomplete, covering, only sales journals and cash receipts, while calculations continued to be performed manually. Although most cash sales procedures had been implemented, the recording of the cost of goods sold had not yet been carried out.